Review of Australian species of Plectranthias Bleeker and Selenanthias Tanaka (Teleostei: Serranidae: Anthiadinae), with descriptions of four new species - Gill, Anthony C.; Pogonoski, John J.; Moore, Glenn I.; Johnson, Jeffrey W. (Zootaxa, 2021)
Australian species of the anthiadine genera Plectranthias and Selenanthias are reviewed. Twenty-two species of Plectranthias and two species of Selenanthias are recorded from Australian waters: Plectranthias sp. 1 from a seamount north of Middleton Reef and Norfolk Ridge, Tasman Sea; P. alleni Randall from off southwest Western Australia; P. azumanus (Jordan & Richardson) from off southwest Western Australia; P. bennetti Allen & Walsh from Holmes Reef, Coral Sea; P. cruentus Gill & Roberts from Lord Howe Island, and possibly off Stradbroke Island, Queensland; P. ferrugineus n. sp. from the North West Shelf and Arafura Sea; P. fourmanoiri Randall from Christmas Island and Holmes Reef, Coral Sea; P. grahami n. sp. from off central New South Wales, Tasman Sea; P. inermis Randall from Christmas Island; P. japonicus (Steindachner) from the Arafura Sea and North West Shelf; P. kamii Randall from the Coral Sea, Lord Howe Island and Christmas Island; P. lasti Randall & Hoese from the North West Shelf and off Marion Reef, Queensland; P. longimanus (Weber) from the Timor Sea, Great Barrier Reef, Coral Sea and southern Queensland; P. maculicauda (Regan) from southeastern Australia; P. mcgroutheri n. sp. from the North West Shelf; P. megalophthalmus Fourmanoir & Randall from northeast of the Whitsunday Islands, Queensland; P. melanesius Randall from southeastern Queensland and a seamount north of Middleton Reef; P. moretonensis n. sp. from off Stradbroke Island, Queensland; P. nanus Randall from the Cocos (Keeling) Islands, Christmas Island, Great Barrier Reef and Coral Sea; P. retrofasciatus Fourmanoir & Randall from the Great Barrier Reef; P. robertsi Randall & Hoese from off Queensland, Coral Sea; P. winniensis (Tyler) from the Great Barrier Reef and Coral Sea; Selenanthias analis Tanaka from the North West Shelf and Arafura Sea; and S. barroi (Fourmanoir) from west of Lihou Reef, Coral Sea. Five of the species represent new records for Australia: P. azumanus, P. kamii, P. megalophthalmus, P. melanesius and S. barroi. Previous records of P. megalophthalmus from the North West Shelf are based on misidentified specimens of P. lasti. Records of P. wheeleri from the North West Shelf are based on specimens here identified as P. mcgroutheri n. sp. A record of P. yamakawai Yoshino from Christmas Island is based on a misidentified specimen of P. kamii. Plectranthias retrofasciatus was previously recorded from the Great Barrier Reef as P. pallidus Randall & Hoese, here shown to be a junior synonym of P. retrofasciatus. Video-based records of P. kelloggi from the Great Barrier Reef appear to be based on P. retrofasciatus. Identification keys, diagnoses, character summaries, photographs and Australian distribution information are presented for all species. Full descriptions are provided for the new species and for those newly recorded from Australia.